MOTOR REHABILITATION OF INVALIDS WITH INFRINGEMENT OF LOCOMOTOR FUNCTION DUE TO RESIDUAL PHENOMENA OF STROKE - G. M. Tsirkin; O. A. Jafarova; V. A. Voroninskiy; M. M. Shperling (Бюллетень сибирской медицины)
This paper demonstrates the clinical efficacy of multiparametric biofeedback in patients aged 45 to 60 years with residual phenomena after stroke with 1 to 5 years prescription. Comparison was made according to the international scale. Patients in the control group and the main group were selected at random.It was shown that the use of multiparametric biofeedback allows to reduce spasticity, restore body image and improve hemodynamics, increase adaptive capacity of the body, improve coordination. At the sa me time, when compared with medical therapy of spasticity, this technology is an order higher cost-effective.